THE ESSENCE OF ECOMARKETING: A COMPREHENSIVE ANALYSIS OF ADVANTAGES AND DISADVANTAGES - Kizi, Ostanakulova Gulsarakhan Muhammadyakub (ANTIS PUBLISHER, 2024)
Ecomarketing became an increasingly popular strategic approach for companies striving to integrate environmentally friendly trends into their business models. This study focuses on the nature of ecomarketing and its role within the business by analyzing current literature and findings to present a detailed overview of the method’s strengths and weaknesses. Our literature review reveals how ecomarketing allows companies to attract target audiences, build brand loyalty, and access new selected segments, as well as others by underpinning the companies’ commitment to the environmental agenda. It also reflects on the possible threats of the ecomarketing policy, such as labeling, corporate reputation, the high costs of production, and the difficulty of measuring the environmental impact